Geotechnical problems due to the collapse of unsaturated soils: the case of loess from northern France - Delage, Pierre (Journal of Applied Engineering Science & Technology, 2014)
Some periglacial loess deposits from Northern France are partially saturated thanks to the protection provided by an upper surface layer with higher clay content. When excavated and exposed to climatic changes, the loess deposit may exhibit collapse if their clay fraction is small enough and carbonate content high enough. These conditions allow for the stability of a loose porous microstructure with bonding links that are destroyed by water infiltration. In the paper, the origin and the properties of loess deposits from Northern France are described, together with the laboratory method of characterising collapse. Some practical conclusions are afterwards drawn. Résumé : Certains dépôts de lœss éoliens périglaciaires du Nord de la France se trouvent dans un état de saturation partielle car ils sont protégés des précipitations par une couche de surface contenant une plus grande proportion d’argile. Quand ils sont mis à nu et exposés aux variations climatiques, ils peuvent, si leur proportion d’argile est suffisamment faible et leur teneur en carbone suffisamment élevée, présenter le phénomène d’effondrement. Ces conditions permettent la stabilité d’une structure poreuse lâche dont les liens de cimentation sont détruits par infiltration d’eau. On décrit l’origine et les caractéristiques de ces lœss et la méthode d’indentification de l’effondrement en laboratoire pour en tirer ensuite quelques conclusions pratiques. Mots clés : Sols non saturés, Loess, effondrement, Laboratoire, oedomètre.
Keywords: Unsaturated soils, loess, collapse, laboratory, oedometer